Konektor Masker : Digital Marketing oleh Ibu Rumah Tangga dalam Upaya Peningkatan Pendapatan Keluarga di Kelurahan Pasar Bengkulu - Barika; Retno Agustina Ekaputri (Kreativasi : Journal of Community Empowerment, 2022)
Doing business or selling mask connectors by housewives requires the right marketing method. The lack of knowledge of housewives about digital marketing inspires the empowerment team to convey information about using digital marketing to sell their products in Kelurahan Pasar Bengkulu. The method of activities used includes socialization and providing training. The results obtained are that housewives in Kelurahan Pasar Bengkulu understand the use of digital marketing and will implement to selling promotion of their mask connectors.